Mediterranean Plants with Antimicrobial Activity against Staphylococcus aureus, a Meta-Analysis for Green Veterinary Pharmacology Applications - Francesca Oppedisano; Rosario De Fazio; Enrico Gugliandolo; Rosalia Crupi; Ernesto Palma; Sayed Haidar Abbas Raza; Bruno Tilocca; Carmine Merola; Cristian Piras; Domenico Britti (Microorganisms, 2023)
Antimicrobial resistance (AMR) has emerged as a global health crisis, necessitating the search for innovative strategies to combat infectious diseases. The unique biodiversity of Italian flora offers a treasure trove of plant species and their associated phytochemicals, which hold immense potential as a solution to address AMR. By investigating the antimicrobial properties of Italian flora and their phytochemical constituents, this study aims to shed light on the potential of phyto-complexes as a valuable resource for developing novel or supportive antimicrobial agents useful for animal production.